Effect of CRISPR/Cas9-Edited PD-1/PD-L1 on Tumor Immunity and Immunotherapy - Xu, Yanxin; Chen, Chen; Guo, Yaxin; Hu, Shengyun; Sun, Zhenqiang (Frontiers in Immunology, 2022)
Clustered regularly interspaced short palindromic repeats/CRISPR-associated nuclease9 (CRISPR/Cas9) gene editing technology implements precise programming of the human genome through RNA guidance. At present, it has been widely used in the construction of animal tumour models, the study of drug resistance regulation mechanisms, epigenetic control and innovation in cancer treatment. Tumour immunotherapy restores the normal antitumour immune response by restarting and maintaining the tumour-immune cycle. CRISPR/Cas9 technology has occupied a central position in further optimizing anti-programmed cell death 1(PD-1) tumour immunotherapy. In this review, we summarize the recent progress in exploring the regulatory mechanism of tumour immune PD-1 and programmed death ligand 1(PD-L1) based on CRISPR/Cas9 technology and its clinical application in different cancer types. In addition, CRISPR genome-wide screening identifies new drug targets and biomarkers to identify potentially sensitive populations for anti-PD-1/PD-L1 therapy and maximize antitumour effects. Finally, the strong potential and challenges of CRISPR/Cas9 for future clinical applications are discussed.